Neurolaw: is the Dialogue between Neuroscience and Law Inevitable? - Dovilė Valančienė (Lithuanian Sports University, 2018)
Research  background  and  hypothesis.  Today,  more  and  more  discussions  arise  about  the  effect  of  a  new science - postmodern, of complex dynamic systems - on the science of law. The law science is encouraged to be open both internally and externally with other sciences. The new science encourages other sciences to seek for dialogue, connection and integration; one example of this is neurolaw. Neurolaw is an association of neuroscience and law science aiming at a clearer understanding and coming closer to the truth than it was before, using the achievements of neuroscience. This is a new association which causes much debate. How can it help the law? Is this just a temporary fashion? These are topical issues for the law science to move towards perfection, and for the neuroscience to be adaptable and very important to other sciences. Research aim. A conceptual overview of the essence of neuroscience and neurolaw, answering the question about how neuroscience can help the law, and if the dialogue between them is inevitable or just a temporary fashion. Research methods. Systematic and logical analysis of the relationship between neuroscience and law. Discussion and conclusions. Neurolaw is an inevitable dialogue between law and neuroscience. This is the integration of the two sciences in order to get a clearer understanding of complex legal issues when we deal with people's destinies, and most important, to answer what is true in a particular case. We cannot say that this is just a temporary fashion, more scientific research is carried out and with the help of this dialogue more cases can achieve the equitable solution. On the other hand, various studies related to the judicial decision-making are important to neurolaw, as they look into how decisions are made, what influences them, etc. Conceptualizing this integration as well as the importance and the scope of the dialogue between these sciences, we can say that law science will inevitably face major changes in this area. The future of this inevitable integration depends on how scientists will be able to communicate and achieve the fairest goals for us. Keywords: integration, changes, the new science.